Keteladanan dan Pengembangan Jiwa Keagamaan Anak Usia Dini di RA Raudlatul Mustarsyidin Gapura Sumenep - Siti Hairiyah; Mukhlis (Institut Kariman Wirayudha Sumenep, 2023)
The religious spirit needs to be nurtured as much as possible so that children's religious development can develop well. Religious spirit refers to a person's spiritual aspect which has significant continuity with faith in God which is reflected in the form of worship to Him. For this reason, it is very necessary to develop a child's religious spirit so that later it can become the basis for doing everything in his life, whether hablumminallah or hablumminannas. The focus of this research is to determine the development of the religious spirit of early childhood through example. The research method used is PTK, researchers take action through the application of role models in the classroom to help develop children's religious spirit. The PTK model that researchers use is the Kurt Lewin model, the PTK pattern that researchers use is a collaborative pattern. The results of the research show that early childhood children at RA B Raudlatul Mustarsyidin experienced a very significant development of their religious spirit, children who were initially unable to perform prayer movements properly and correctly became able, children who initially spoke harshly to others became able to speak slowly and politely, children those who initially didn't care about their friends became concerned, and so on. This is in accordance with the data, namely that 10 children's religious souls are very good, 10 children's religious souls are good, and 3 children's religious souls are quite good.